Β-FeSe nanorods composited g-C3N4 with enhanced photocatalytic efficiency. Issue 3 (13th March 2019) - Shen, Shijie; Zhong, Wenwu; Wang, Zongpeng; Lin, Zhiping; Feng, Shangshen
Abstract : A series of β-FeSe nanorods composited g-C3 N4 were prepared. The structure, morphology, chemical state, photocatalytic activity, electrochemical impedance and photoluminescence of β-FeSe/g-C3 N4 composites were well characterized. It is found that the decolourization rate of 3 wt% β-FeSe/g-C3 N4 composites reaches 4.4 times than that of g-C3 N4 . The improved photocatalytic properties could be ascribed to the reduced recombination of photogenerated electrons and holes, which is derived from the excellent ability of β-FeSe to capture and transfer electrons. This work provides an alternative co-catalyst for decolourizing organic matter.